2017
DOI: 10.1002/2017ja024482
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Magnetic Flux Ropes Via Magnetic Reconnection Observed at the Magnetopause

Abstract: Using the high‐resolution field and plasma data obtained from the Magnetospheric Multiscale mission at the magnetopause, a series of three flux transfer events was observed one after another inside southward ion flows, without time gap between any two successive flux ropes. Using the plasma measurements, the current densities within the flux ropes were studied in detail. The currents within the first two flux ropes, dubbed Fr1 and Fr2, were composed of a series of well‐separated filamentary currents. The thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 69 publications
(109 reference statements)
6
41
0
Order By: Relevance
“…Similarly, at the dayside magnetopause, multiple FTEs are believed to form due to the reconnection process and evolve into larger structure over time (Fu & Lee, ). Previous studies have determined the size distribution and flux content of FTEs (e.g., Eastwood et al, , ; Fermo et al, ; Hasegawa et al, , ; Pu et al, ; Wang et al, , ). These results indicate that FTEs are one to few Earth radii in size and contain 1–10 MWb in magnetic flux.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, at the dayside magnetopause, multiple FTEs are believed to form due to the reconnection process and evolve into larger structure over time (Fu & Lee, ). Previous studies have determined the size distribution and flux content of FTEs (e.g., Eastwood et al, , ; Fermo et al, ; Hasegawa et al, , ; Pu et al, ; Wang et al, , ). These results indicate that FTEs are one to few Earth radii in size and contain 1–10 MWb in magnetic flux.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic simulations and in situ observations have suggested that, upon generation, flux ropes in three dimensions evolve in response to their environment moving tailward with the magnetosheath flow and expanding as the external pressure relaxes toward solar wind values (e.g., Berchem & Russell, 1984;Rijnbeek et al, 1984;Zhao et al, 2016;Farrugia et al, 2016;Teh, Nakamura, et al, 2017) and coalescence (e.g., Finn & Kaw, 1977;Karimabadi et al, 2011;Pritchett, 1992;Song et al, 2012;Wang et al, 2017;Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the other scenario, depicted in Figure 1c, the magnetic islands grow via coalescence. Chains of ion-scale FTEs (Milan et al, 2000;Slavin et al, 2012;Dong et al, 2017;Teh, Denton, et al, 2017;Wang et al, 2017;Hwang et al, 2018) are formed at the dayside magnetopause due to multiple X-line reconnection (Lee & Fu, 1985). In this scenario, the neighboring FTEs are forced to merge, reconnect, and grow into larger The shading of the islands determines the thermal pressure p inside them with the darkest shades indicating the region of largest p. The number of circles per area indicates magnetic field magnitude and the gradient shading inside the islands shows plasma pressure variability across the structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Magnetospheric Multiscale (MMS) mission with its unprecedented high-resolution plasma measurements provides a good opportunity to study the structure of ion-scale flux ropes with a duration of a few seconds in the data (e.g., Alm et al, 2018;Eastwood et al, 2016;Teh et al, 2017;Wang et al, 2017), which present observations of current filaments, nonideal ion behaviors, wave activities and even flux rope coalescence. An ion-scale craterlike flux rope has also been resolved by MMS, which is interpreted as a result of the depression of transverse magnetic fields in a flux rope simulation (Teh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%